2012
DOI: 10.1016/j.bbrc.2012.09.125
|View full text |Cite
|
Sign up to set email alerts
|

Green tea inhibits cycolooxygenase-2 in non-small cell lung cancer cells through the induction of Annexin-1

Abstract: Elevated cyclooygenase-2 (COX-2) expression is frequently observed in human non–small cell lung cancer (NSCLC) and associated with poor prognosis, indicating critical involvement of the inflammatory pathway in lung carcinogenesis. Recently, we found that green tea extract (GTE) induced annexin-1 (ANX1) in the lung adenocarcinoma A549 cells. ANX1 is a glucocorticoid-inducible 37 kDa protein involved in a wide range biological function and is an important anti-inflammatory mediator. The present study further exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Here, we found that GTP intake was also associated with these parameters, except for VEGF-A expression. GTP was previously found to inhibit tumor growth [ 35 ], angiogenesis, [ 36 ], and COX-2 [ 37 ] and HO-1 [ 38 ] expression under pathological conditions including malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that GTP intake was also associated with these parameters, except for VEGF-A expression. GTP was previously found to inhibit tumor growth [ 35 ], angiogenesis, [ 36 ], and COX-2 [ 37 ] and HO-1 [ 38 ] expression under pathological conditions including malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, silencing annexin A1 expression overturned the inhibitory effect of GTE on COX-2. These results suggest that GTE shows its effect through inducing annexin A1 expression, therefore targeting annexin A1 could be a promising mechanism in preventing lung cancer [98].…”
Section: Annexin-targeted Studiesmentioning
confidence: 77%
“…After Cmp17b treatment, the Ptgs2 expression is downregulated in the aorta, possibly underpinned by the anti-inflammatory effects of FPR agonists. Specifically, this effect of Cmpd17b may be independent of diabetes as it has been reported that upregulation of the endogenous FPR agonist, Annexin A1, reduces Ptgs2 expression in lung cancer cells [50]. Despite observing a greater functional contribution of prostanoids to endothelium-dependent relaxation in Cmpd17b-treated diabetic mice, a compensatory downregulation of mRNA for prostacyclin synthase (PTGIS) was observed, without affecting Ptgs1 expression.…”
Section: Discussionmentioning
confidence: 91%